William James: a re-examination of The Varieties of Religious Experience. Issue 4 (21st April 2017) - Kay, William K.
ABSTRACT: The centenary edition of William James' classic account of religious experience, The Varieties of Religious Experience: A Study in Human Nature, was first published by Routledge in 2002 with a new forward as well as the preface of the original 1902 edition. This paper reviews aspects of James' work and briefly considers its later development.